Audição de jovens de 18 a 25 anos: estudo do entalhe audiométrico - Sousa, Gisely Belich de (2009)
Introduction: In recent years, has been increasing the concern of Audiologists related to the hearing health of youngsters exposed to urban noise and loud music, which provokes auditory and extra-auditory effects. It is been more and more common for young people who undergo pure tone audiometry to present hearing thresholds above OdB HL, eloser to 20 or 25 dB HL, showing the audiometric notch. This is a hearing reduction within the normal limit, in the frequencies of 3k, 4k or 6 kHz, in presence of a difference of at least 10 dB from the precedent or following the analyzed frequency. The audiometric notch may indicate a tendency of development of noise induced hearing loss with time. Objective: To identify the presence of the audiometric notch in youngsters from 18 to 25 years old, through pure tone audiometry performed at a private hospital in São Paulo, from 2005 to 2007, verifying if gender, frequency, ear and type of notch are sources of variability. Method: This study is retrospective, quantitative and the procedure consisted in the investigation of 722 audiograms of normal hearing subjects,being 353 (48.9%) female and 369 (51.1%) males. Results: The hearing notch was present in 390 (54%) of the 722 studied sample, being more prevalent for female (223 -57.2%) than male (167 - 42.8%). There were statistically significant differences between hearing thresholds for the frequencies: 4, 6, 8 kHz in the right ear and in the left ear, for the frequencies of 1 and 4 kHz. The prevalence of audiometric notch type unilateral - 308 (79%), with lhe bilateral type present in only 21%. Conclusion: The results showed statistically significant difference in the presence of audiometric notch between gender, ears, frequency and type of hearing notch, suggesting that this population may be at risk for future hearing losses, if adequate measures are not taken in order to preserve their hearing health